Abrogation in the Quran: Perspectives of Jamal Al-Banna and Jasser Auda - Shohib Khoiri; Syed Mohammad Chaedar Syed Abdurrahman Al Yahya; Muhammad Yusry Affandy Md Isa; Nusairah Ramli (Universiti Sains Islam Malaysia, 2024)
Maʿālim Al-Qurʾān Wa Al-Sunnah, Volume 20 Issue 1 Page (85-106)